Behavior Modification in Children with Eating Behavior Disorder (Pica Disorder): A Literature Study - Mukarromah, Tsali Tsatul (JIV-Jurnal Ilmiah Visi, 2022)
Pica disorder, which is less aware of by parents because of the assumption that children include and eat non-food items (soil, paper, dirt, gravel, etc.) in children. Then, the impact of this behavior disorder can hinder the child’s development and can endanger the child’s health if not immediately. This study aims to determine the appropriate treatment for eating behavior (behavior disorders) in children through several studies examining this. The method used in this research is literature study by searching and studying various sources of literature in the form of scientific data which are then entered and analyzed. The results of the study found that the application of behavior modification with prevention, system blocking, and reinforcement by keeping children away from non-food objects around them and using tools to control their behavior, thereby reducing pica behavior. However. The use of this method is not guaranteed to prevent eating disorders (pica disorders).